ANALISIS BREAK EVEN TERHADAP PENJUALAN JASA SEWA KAMAR PADA HOTEL ANGING MAMMIRI MAKASSAR - siti marhumi; Muh Firmansyah; Moh Aris Pasigai (Jurnal Ilmu Manajemen Profitability, 2017)
This study aimed to calculate the break-even level on Hotel Anging Mammiri, especially on the sales room rental services in 2014, which includes the sale room rental services Happy Suite, Deluxe, Superior and Standard rooms. From the results of this study are expected to know the level of sales of rental services at the Hotel Anging Mammiri. This analysis aims to calculates the level of sales so that the proceeds equal to the sum of all variable costs and fixed costs. In calculating the break even at Hotel Anging Mammiri author using the equation engineering approach. To allocate fixed costs and variable costs the author uses the method relative sales value. Break-even analysis can be used by the hotel management as a material consideration in planning for short-term profit, primarily as a guide so that the sale of the hotel room rental services do not suffer losses or at least not in a state to break even. From the results of this analysis can also be known effect of changes in rental prices per type of room to break-even analysis, which can later be used to determine price changes Which types of rooms that can generate greater profits. Thus the results of break-even analysis can be used to assist management in profit planning.